MODEL TUDANG SIPULUNG DALAM PEMBELAJARAN ISLAM DAN KEARIFAN LOKAL - Yunus Yunus (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
The research aims to explore the concept of local wisdom education with the tudassipung (sitting together) model. This study uses a qualitative method with an ethnopedagogical approach. The technique of collecting data through interviews, interviewed informants came from several groups, from academics (lecturers) as many as 6 people, students from several ethnic groups, 4 from Toraja, 4 from Rongkong, 9 from Bugis and 8 from students. Researchers also interviewed 6 community leaders. The result of the research is that learning Islam and local wisdom using the tudassipulung model is quite effective. This can be seen from the assessment of 5 (five) aspects, namely attitudes, interests, self-concept, values, and morals with 5 levels, namely: receiving, responding, valuing, organization, characterization